2013
DOI: 10.1007/s00018-013-1508-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the insulin-like growth factor (IGF) axis in osteogenic and odontogenic differentiation

Abstract: The insulin-like growth factor (IGF) axis is a multicomponent molecular network which has important biological functions in the development and maintenance of differentiated tissue function(s). One of the most important functions of the IGF axis is the control of skeletal tissue metabolism by the finely tuned regulation of the process of osteogenesis. To achieve this, the IGF axis controls the activity of several cell types—osteoprogenitor cells, osteoblasts, osteocytes and osteoclasts to achieve the co-ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…However, little is known about the effects and molecular mechanisms of IGFBP7 in stem cells (22). Therefore, we investigated its effects on the osteogenic differentiation of BMSCs.…”
mentioning
confidence: 99%
“…However, little is known about the effects and molecular mechanisms of IGFBP7 in stem cells (22). Therefore, we investigated its effects on the osteogenic differentiation of BMSCs.…”
mentioning
confidence: 99%
“…Various growth factors can mediate the osteo/dentinogenic differentiation of MSCs2345, including stem cells from apical papilla (SCAPs)6. These SCAPs can differentiate into odontoblasts or osteoblasts in vitro , and form dentin-like tissues along with tooth root-like structures in vivo 137.…”
mentioning
confidence: 99%
“…One of the polypeptide growth factors (i.e., IGF-1) is the most important member of this axis7. Previous studies have revealed that IGF-1 can significantly enhance the odonto/osteogenic differentiation of SCAPs, periodontal ligament stem cells (PDLSCs) and dental pulp stem cells (DPSCs)689.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Secretion of insulin-like growth factor and associated proteins may promote GH secretion, which in turn promotes the conversion of osteoblasts. 26 In this study, we describe osteocalcin as a biomarker used to assess the treatment efficacy of GH deficiency, precocious puberty, abnormalities of glucocorticoid, and nutritional rickets, and is also a sensitive index for bone growth in OSAHS. 27,28 Previous studies have demonstrated that OSAHS alters the sleep state, increasing slow wave sleep (SWS), which results in depressing GH secretion, as GH secretion is known to peak in SWS.…”
Section: Discussionmentioning
confidence: 99%